A Self-Dialogue with the Thoughts of Paulo Freire: A Critical Pedagogy Encounter - Yolanda Samacá Bohórquez (Asociación Colombiana de Profesores de Ingles, 2020)
This paper develops a two-voiced self-dialogue with some compelling ideals of critical pedagogy advocated by Paulo Freire: reflection, dialogue, conscientização, (conscientization) praxis, critical engagement, and transformation. This dialogue, as a critical pedagogy encounter, has allowed me to go through a process of self-criticism or hopefully a self-recognition of understandings, experiences, constructions, co-constructions, and reconstructions of my practices as a language educator. I will address the following evolving choices: On dialogue and critical pedagogy, from language as power to language as possibility, from instrumental to alternative critical pedagogy practices towards more critical understandings and doings of education.